Digital Referral System and Consumer Acquisition, Engagement, and Loyalty of Selected Online Business Platforms: Inputs to Enhanced Strategies (Focus on Shopee, Lazada, and Temu) - Galolo, Kent Marie; Garcia, Pamela Bianca C.; Hipolito, Mhicaela E.; Insigne, Rosa May C.; Martorillas, Jayrowe; Viril, Christian Andre (International Journal of Sustainability and Advanced Integrated Research, 2026)
The rapid expansion of the digital economy has transformed the way online business platforms attract and retain consumers. Digital referral systems have emerged as an effective marketing strategy that encourages existing users to recommend products and services to potential customers through incentive base programs. This study examines the relationship between digital referral systems and consumer acquisition, consumer engagement, and consumer loyalty among users of selected online business platforms, specifically Shoppee, Lazada, and Temu. The research evaluated digital referral systems in terms of incentive, and reward structure, ease of use, and the accessibility, social sharing features, tracking and analytical capabilities, and security and privacy of referral data. Consumer acquisition was assessed based on the reach of new customers, conversion of referred needs, brand awareness, cost efficiency, and referral influence on purchase decision. Consumer engagement was evaluated through interaction with referral content, frequency of participation, feedback activity, community involvement, and consistency of platform of usage, while consumer reality was measured through repeat purchase behavior, brand advocacy, emotional attachment, retention of referred customers, and switching intention. A quantitative research design utilizing a structure survey questionnaire was employed to gather data from 377 respondents selected through purposive sampling. Statistical analysis revealed that digital referral system were High Evident across all measured dimensions. Furthermore, Pearson Product-Moment Correlation Analysis indicated a significant positive relationship between digital referral systems and consumer acquisition (r=0.820, p
Keywords: Digital Referral Systems, Consumer Acquisition, Consumer Engagement, Consumer Loyalty, Online